Gambaran Aktivitas Fisik dan Pola Makan Selama Pandemi Covid-19 pada Remaja - Anissa Reza Miranda; Ajeng Kartika Sari (UPT Publikasi Ilmiah Unisba, 2022)
Abstract. Covid-19 is an infectious disease caused by the Coronavirus 2 of the Severe Acute Respiratory Syndrome. It was predicted to appear in 2020. As a result of the pandemic, Work From Home has been established for the entire population, including youths and students who are afflicted. Restrictions on outside activities resulted in a variety of lifestyle modifications, including changes in physical activity and food. A high-calorie diet combined with insufficient physical activity might cause health concerns in teens. The goal of this study is to look at the description of physical activity and eating patterns in adolescents at SMA Negeri 4 Metro during the pandemic. This study is descriptive in nature. Proportional stratified random sampling was used to determine the sample size in this investigation. The Global Physical Activity Questionnaire and the Food Frequency Questionnaire were used to collect data. This study found that during the Covid-19 epidemic, 56.4 percent of teenagers engaged in moderate physical activity, 22.7 percent engaged in high physical activity, and 10.9 percent engaged in poor physical activity. Adolescents who engage in moderate to high physical activity eat foods with a typical number of calories, whereas adolescents who engage in low physical activity eat foods with a high number of calories. During the Covid-19 epidemic, teenagers ate breakfast six times per week, snacks three times per week, fast food three times per week, and supplements and veggies three times per week. Abstrak. Covid-19 merupakan penyakit menular yang disebabkan oleh Severe Acute Respiratory Syndrome Coronavirus 2 dan ditetapkan menjadi pandemi pada tahun 2020. Pandemi ini menyebabkan ditetapkannya Work From Home untuk seluruh masyarakat, termasuk remaja atau siswa yang bersekolah. Pembatasan aktivitas di luar rumah mengakibatkan terjadinya beberapa perubahan pola hidup termasuk perubahan aktivitas fisik dan pola makan. Pada remaja yang aktivitas fisiknya sedikit dengan pola makan yang memliki kalori tinggi dapat menyebabkan permasalahan kesehatan. Penelitian ini bertujuan untuk menganalisis bagaimana gambaran aktivitas fisik dan pola makan selama pandemi pada remaja di SMA Negeri 4 Metro. Penelitian ini merupakan penelitian deskriptif. Besar sampel dalam penelitian ini diambil dengan cara Proportionate Stratified Random Sampling. Data dikumpulkan dengan menggunakan Global Physical Activity Questionnaire dan Formulir Food Frequency Questionnaire. Hasil yang didapatkan dalam penelitian ini yaitu jumlah presentase remaja selama pandemi Covid-19 melakukan aktivitas fisik sedang sebayak 56.4%, aktivitas fisik tinggi 22.7% dan aktivitas fisik rendah 10.9%. Remaja dengan aktivitas fisik sedang dan aktivitas tinggi mengkonsumsi makanan dengan jumlah kalori yang normal, sedangkan remaja beraktivitas fisik rendah mengkonsumsi makanan dengan jumlah kalori tinggi. Kebiasaan pola makan remaja selama pandemi Covid-19 adalah mengkonsumsi sarapan sebanyak 6 kali/minggu, mengkonsumsi jajan sebanyak 3-5 kali/minggu, mengkonsumsi Fastfood sebanyak 3-5 kali/minggu dan mengkonsumsi suplemen dan sayur sebanyak 3-5 kali/minggu.